Discovering Kražiai Residents: The Story of a House and a Family - Kvietkuvienė, Emilija; Tamulaitis, Rimvydas (Lietuvos istorijos studijos, 2025)
By referring to sources of oral history, the story of a house in Kražiai, a minor Lithuanian town, is traced back from its construction during the interwar period up to the present day, while revealing the fate of its residents as well as their role in Kražiai during the interwar period and in the afterwar years. Kražiai town residents can still remember the two teachers, Michalina Petrusevičiūtė and Stanislava Petrusevičiūtė, who used to dwell there. The memories of the locals can help reveal the personalities of the two teachers and even grasp the inner tension they were experiencing, stemming from the complex inner world, and triggered by the fatal events of the time, involving the occupation of Lithuania and the afterwar years. The two personalities also serve to reveal the proof of importance of a teacher as a bearer of a certain status in society, a teacher’s personality and function in the life and daily routine of the small town. Meanwhile, the history of the Petrusevičiai family house opens up an opportunity to touch not only the stories of its residents but also history of the material culture of the small Lithuanian interwar towns, which serves as inspiration to take a closer glance at Kražiai town during the interwar years and its residents as typical representatives of a small town. A single house and its residents may open up an entire epoch, or at least some eloquent episodes of that period.